Surface Treatment of Cu:NiOx Hole-Transporting Layer Using β-Alanine for Hysteresis-Free and Thermally Stable Inverted Perovskite Solar Cells - Galatopoulos, Fedros; Papadas, Ioannis T.; Ioakeimidis, Apostolos; Eleftheriou, Polyvios; Choulis, Stelios A. (My University, 2020)
Inverted perovskite solar cells (PSCs) using a Cu:NiOx hole transporting layer (HTL) often exhibit stability issues and in some cases J/V hysteresis. In this work, we developed a β-alanine surface treatment process on Cu:NiOx HTL that provides J/V hysteresis-free, highly efficient, and thermally stable inverted PSCs. The improved device performance due to β-alanine-treated Cu:NiOx HTL is attributed to the formation of an intimate Cu:NiOx/perovskite interface and reduced charge trap density in the bulk perovskite active layer. The β-alanine surface treatment process on Cu:NiOx HTL eliminates major thermal degradation mechanisms, providing 40 times increased lifetime performance under accelerated heat lifetime conditions. By using the proposed surface treatment, we report optimized devices with high power conversion efficiency (PCE) (up to 15.51%) and up to 1000 h lifetime under accelerated heat lifetime conditions (60 °C, N2).
Keywords: Amino acids; Charge traps; Degradation; Hysteresis; Metal oxides; Oxygen vacancies; Perovskite solar cells; Surface treatment; Thermal stability; β-alanine